Surgical Management of Plaque Induced Gingival Enlargement: A Case Report - Mellani Cindera Negara; Revina Daniella Dwi March (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2022)
Introduction: Gingival enlargement or gingival overgrowth, a common trait of gingival disease, is characterized by an increase in the size of gingiva with multifactorial etiology. Purpose: This case report aimed to discuss gingival enlargement case along with the treatment plan of the patient.Case presentation: A 50-year-old female patient reported the swelling in the gums of teeth in lower front region since six months ago. Gingival enlargement was treated with modified Widman flap procedure, internal bevel incision, and bone recontouring. These treatment modalities showed significant clinical improvement in the form of pocket depth reduction and gingival contour Conclusion: Dental plaque bacteria served as initial factor of inflammation which induce the occurrence of gingival enlargement. Surgical treatment can be done if the initial phase still presenting gingival enlargement with firm consistency with minimum inflammation.